Phonological awareness: Cross-linguistic comparisons with a focus on Spanish - Clinton, Amanda (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
The purpose of the present literature review is to highlight differences and similarities in fundamental reading processes depending upon the language of the learner. Specific attention is paid to contrasts between the relatively opaque English language and more transparent languages, with a specific focus on Spanish. Analysis of the literature indicates a steeper developmental curve in languages such as Spanish, although processes are similar. Findings highlight the way in which a more opaque native language could inform learning of a second, more transparent language.